1998
DOI: 10.1016/s0022-5347(01)63982-x
|View full text |Cite
|
Sign up to set email alerts
|

SEX DIFFERENCES IN FUNCTION AND DISTRIBUTION OF beta-ADRENOCEPTORS IN RABBIT URINARY BLADDER

Abstract: These findings demonstrate that there are sex-related differences in the function and the distribution of beta-adrenoceptors in rabbit trigonal smooth muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In a previous study (Atalık et al, 1999), we observed intracellular Ca 2+ pools may play a functional role in the cooling-induced contractions of rabbit detrusor smooth muscle. Furthermore, in literature sex-related differences in function and distribution of beta-adrenoceptors in rabbit urinary bladder (Morita et al, 1998). Although female rats were used in our experiments, the findings were in line with other reports in male rats (Hellstrom et al, 1991;Mustafa and Thulesius, 1999), indicating that there are not sex-related differences in the function of rat detrusor during cooling.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study (Atalık et al, 1999), we observed intracellular Ca 2+ pools may play a functional role in the cooling-induced contractions of rabbit detrusor smooth muscle. Furthermore, in literature sex-related differences in function and distribution of beta-adrenoceptors in rabbit urinary bladder (Morita et al, 1998). Although female rats were used in our experiments, the findings were in line with other reports in male rats (Hellstrom et al, 1991;Mustafa and Thulesius, 1999), indicating that there are not sex-related differences in the function of rat detrusor during cooling.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the efficacy of isoprenaline had also been numerically smaller in female as compared to male rats in a previous study; while this trend had consistently been observed with four different agonists including isoprenaline, it had reached statistical significance only for the partial agonists BRL 37,344 and CGP 12,177 (Frazier et al, 2006). On the other hand, a study in rabbits did not detect gender differences in isoprenaline-induced detrusor relaxation, but within that study relaxation responses in the trigone were significantly greater in female than male samples (Morita et al, 1998). Thus, there is insufficient evidence for solid conclusions regarding a possible difference in β-adrenoceptor-mediated detrusor relaxation.…”
Section: Discussionmentioning
confidence: 95%
“…In view of these observations the importance of water intake and consequently urine production, on the function of the bladder has been extended by Ohnishi et al [1999] who demonstrated explicitly that diuresis causes an increase in contractile strength consequently protecting the bladder from the contractile dysfunction associated with partial obstruction. In addition to the in¯uence of diuresis noted above, it is appropriate to consider that there are gender differences in the central and peripheral distribution of receptors [Latifpour et al, 1990;Vaughan and Satchel, 1995;Morita et al, 1998] that may affect the contractile function of the bladder. In addition to variations in a and b receptors contractility may be in¯uenced by estrogen and NO shown to reduce bladder blood¯ow [Pontari and Ruggieri, 1999] and whole body production of NO is greater in healthy women than in men [Forte et al, 1998].…”
Section: Discussionmentioning
confidence: 99%